2015
DOI: 10.1161/atvbaha.114.304591
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Individuals With and Without Type 2 Diabetes Mellitus Present Generalized Vascular Dysfunction

Abstract: Objectives— The first objective of this study was to demonstrate differences within endothelial-dependent and endothelial-independent vasoreactivity in macro- and microcirculation beds among patients with metabolic syndrome (MetS) with and without type 2 diabetes mellitus (T2D) compared with healthy counterparts. The second objective was to determine relationships among the function of macro- and microvascular systems and abdominal adiposity, as well as inflammatory markers in the 3 groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 34 publications
2
93
2
2
Order By: Relevance
“…27 Microvascular endothelial reactivity assessment is essential for investigating the pathophysiology of diabetes and cardiovascular diseases. 29,30 In the present study, microvascular endothelial function was evaluated using LSCI, which represents an innovative approach to the noninvasive evaluation of microvascular endothelial function. 31-33 A major advantage of this technique is that the reproducibility of LSCI is superior to earlier procedures, such as laser Doppler flowmetry and laser Doppler imaging.…”
Section: Discussionmentioning
confidence: 99%
“…27 Microvascular endothelial reactivity assessment is essential for investigating the pathophysiology of diabetes and cardiovascular diseases. 29,30 In the present study, microvascular endothelial function was evaluated using LSCI, which represents an innovative approach to the noninvasive evaluation of microvascular endothelial function. 31-33 A major advantage of this technique is that the reproducibility of LSCI is superior to earlier procedures, such as laser Doppler flowmetry and laser Doppler imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Central adiposity, rather than changes in blood glucose, was found to be a predictor for this exacerbated vascular phenotype. 6 These two studies highlight the impact of diabetes on vascular cells in humans, and suggest that these cells are responsive to extracellular perturbations associated with the diabetic environment and that hyperglycemia is unlikely to be solely responsible for vascular dysfunction associated with diabetes.…”
Section: Novel Pathways For Vascular Cell Perturbations In Diabetesmentioning
confidence: 95%
“…Bretón-Romero et al 61 showed that wingless-type family member 5a/c-jun N terminal kinase pathway contributed to endothelial dysfunction associated with diabetic patients. Walther et al 62 demonstrated that not only endothelium-dependent but also endotheliumindependent vasodilatations in both micro-and macrocirculation were impaired in association with systemic inflammation in patients with metabolic syndrome with diabetes mellitus.…”
Section: Diabetes Mellitusmentioning
confidence: 99%